An Intramolecular Radical C–N Coupling by N-Iodosuccinimide - Bera, Shyamal Kanti; Bhanja, Rosalin; Sahu, Chandan Chittapriya; Mal, Prasenjit (Synthesis, 2023)
A useful method for the formation of benzimidazole-fused phenanthridines through an intramolecular coupling of unactivated C(sp2)–H and N(sp3)–H bonds using N-iodosuccinimide (NIS) in trifluoroethanol (TFE) is presented. The synthesis of benzo[4,5]imidazo[1,2-f]phenanthridines from 2-([1,1′-biphenyl]-2-yl)-1H-benzo[d]imidazole derivatives is mild, efficient, and sustainable, with high yields and minimal waste generation. The control experiments and EPR studies were aimed at rationalizing the radical pathway of the reaction. Specifically, the use of 1,1-diphenylethylene, TEMPO, BHT, and DMPO as a free-radical spin-trapping reagent in EPR studies, allowed us to conceive a radical pathway. The gram-scale synthesis further supported the practical utility of the methodology for the field of synthetic chemistry.
Keywords: benzimidazole-fused phenanthridines; C–N coupling; TFE; N-iodosuccinimide; radical cyclization